2005
DOI: 10.1123/tsp.19.3.303
|View full text |Cite
|
Sign up to set email alerts
|

Professional Judgment and Decision Making: The Role of Intention for Impact

Abstract: The field of applied sport psychology has recognized the growing consensus that professional autonomy and discretion brings with it the need to train, regulate, and evaluate practice (Evetts, 2001). However, research into how practitioners’ professional judgment is formed and the decision-making processes involved has not received concurrent attention. This paper illustrates some of the possible outcomes and implications for applied sport psychologists from consideration of Professional Judgment and Decision M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 0 publications
2
77
0
Order By: Relevance
“…Research has highlighted that coach behaviour is (or should be) a subtle blend of components designed to provide a bespoke solution to the specific challenges of coaching context (Abraham & Collins, 2011;Martindale & Collins, 2005, Collins & Collins, 2012,2013, 2015. These authors have suggested that the process through which this optimum blend is derived is a combination of nested decision making processes referred to as Professional Judgement and Decision Making (PJDM).…”
Section: Professional Judgement and Decision Making In Sports Coachinmentioning
confidence: 99%
“…Research has highlighted that coach behaviour is (or should be) a subtle blend of components designed to provide a bespoke solution to the specific challenges of coaching context (Abraham & Collins, 2011;Martindale & Collins, 2005, Collins & Collins, 2012,2013, 2015. These authors have suggested that the process through which this optimum blend is derived is a combination of nested decision making processes referred to as Professional Judgement and Decision Making (PJDM).…”
Section: Professional Judgement and Decision Making In Sports Coachinmentioning
confidence: 99%
“…According to Carson and Collins (2011), this represents a time to consider "the need for and direction of change" (p. 149). Crucially, exploring alternative factors must also be included when constructing a case formulation (Martindale & Collins, 2005). As sport psychologists are well aware, suboptimal performance is not necessarily rooted in consistent technical errors (e.g., Cresswell & Eklund, 2006;Wanlin, Hrycaiko, Martin, & Mahon, 1997), nor do circumstances always permit the time required to implement technical refinements with long-term permanence and pressure resistance, a process that may take up to 12 months depending on the complexity of the sport (e.g., number of different skills required by the athlete, such as the singular skill of long jumping vs.…”
mentioning
confidence: 99%
“…From a sports perspective, expertise and professional judgment and decision making have already been well-examined in sport psychology [53,54], coaching [26], and strength and conditioning [55], and therefore provide a strong base from which these approaches can be exploited. There are also, notably, training and evaluation methods already available in the public domain [27].…”
Section: Resultsmentioning
confidence: 99%